Effects of high hydrostatic pressure treatment on in vitro digestibility and in vivo glycemic response of sweet potato flour - Chi-Pei Wu; Bo-Chi Huang; Chin-Lin Hsu; Chung-Yi Wang (Applied Food Research)
Sweet potato is a rich source of resistant starch, fibre, vitamins and minerals, which is associated with healthy benefits. In this study, the effects of high hydrostatic pressure (HHP) treatment at 200–600 MPa on the digestibility of sweet potato flour (SPF) through starch composition analysis, in vitro digestion assays, and glycemic index (GI) and response in diabetic mice. Changes in the morphology of starch granules post-treatment were observed using an scanning electron microscope (SEM). Treatments at 400 and 600 MPa increased amylose in sweet potato starch and significantly increased the proportion of slowly digestible starch (SDS), as indicated by in vitro digestion assays. Resistant starch content decreased, with no significant change in rapidly digestible starch. Peak glucose levels in diabetic mice post-consuming SPF treated at 400 and 600 MPa were 476 and 514, respectively, significantly lower than 608 in the control group. The area under the curve (AUC) of 400 MPa treated-SPF is 14% lower than control SPF. The GI of SPF in the control group was 78.6, reducing to 66.2 and 68.3 post-HHP treatment at 400 and 600 MPa, respectively, with no significant difference in the 200 MPa group from that of the control group. SEM observations showed that damage to starch granules increased with increasing processing pressure. HHP caused the starch granules to gelatinize and recoagulate, forming an irregular shape. The HHP treatment changed the composition of SPF, significantly increasing SDS content and it stabilized postprandial blood glucose levels and reduced GI, rendering it a potential method to develop processed products of sweet potatoes with a low GI, providing a novel technical option for developing health-promoting products.